Agromorphological Diversity of 27 Cassava Cultivars (Manihot esculenta Crantz) in Bengamisa Region, Tshopo In DR Congo - V, Lomboko; J-P, Mukandama; J, Okadjalonka; J-C, Monzenga; M, Molongo; A, Okungo (Budapest International Research in Exact Sciences (BirEx) Journal, 2024)
In the Democratic Republic of Congo (DRC), cassava occupies a particularly important place in the diet of rural households that produce it. 27 local cassava cultivars collected in 08 agricultural production basins in the Bengamisa region were evaluated agro-morphologically. The objective was to analyze the phenotypic diversity of local cassava cultivars and their structuring on the basis of 20 variables selected from cassava descriptors. The collected local cassava cultivars were evaluated in a randomized complete block design with 27 treatments and four replications in Bengamisa. Descriptive analysis of qualitative characters revealed polymorphism between local cassava cultivars. Principal Component Analysis (PCA) showed that the 20 morphological descriptors considered were the most relevant (CP ≥30%) to explain the morphological variability between local cassava cultivars. The ascending hierarchical classification (CAH) made it possible to obtain 4 morphogroups that are relatively undifferentiated compared to the extent of the morphological space between the different agricultural production areas. Discriminant factor analysis (DFA) was carried out using the 3 quantitative production variables (number of tuberous roots per plant; weight of tuberous roots per plant; and plant height at harvest) studied in 4 groups defined by the hierarchical ascending classification and allowed through the Wilks Lambda test to reveal that the 3 descriptors or variables have a very highly significant contribution (p-0.000). These groups offer a great possibility of choosing parents for the creation of improved varieties of cassava with high yield potential and adapted to different agricultural production basins in the Bengamisa region; Tshopo; DR CONGO.